EFEKTIVITAS WORKPLACE STRETCHING EXERCISE DALAM MENURUNKAN TINGKAT RISIKO ERGONOMI (SKOR RULA) PADA KARYAWAN CV PANGLONG KAYU PUTRI DAMAI - Rinaldi Prima Saputra; Zulfikar Zulfikar; Fatimah Wahab Aliun; Rina Mayang Sari; Henry Widagdo; Maulana Ahsan Fadhail (Ensiklopedia of Journal, 2026)
Background: Wood processing workers face high ergonomic risks that trigger musculoskeletal disorders. This study evaluates the effectiveness of Workplace Stretching Exercise (WSE) in reducing RULA scores among employees at CV Panglong Kayu Putri Damai. Methods: This quasi-experimental study used a two-group pretest-posttest design. A sample of 50 male operational workers was divided equally into a control group (n = 25) and an intervention group (n = 25). Data were assessed using the Rapid Upper Limb Assessment (RULA) and analyzed using the Mann-Whitney U test. Results: The control group experienced a significant increase in RULA scores from 5.60 to 5.92 (p = 0.000). Conversely, the intervention group showed a significant decrease from 5.64 to 2.88 (p = 0.000). However, comparative analysis showed no statistically significant difference between the two groups (p = 0.205). Conclusion: WSE effectively reduces ergonomic risks internally, but physical stretching alone is insufficient to produce a statistically superior outcome without accompanied engineering modifications at the workplace. Keywords: Ergonomics, Musculoskeletal Disorders, RULA, Workplace Stretching Exercise